2003
DOI: 10.1152/physrev.00033.2002
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Pulmonary Epithelial Integrins: From Development to Disease

Abstract: Signals from integrins are now known to play critical roles in virtually every aspect of the behavior of epithelial cells, including survival, proliferation, maintenance of polarity, secretory differentiation, and malignant transformation. The cells that line the conducting airways and alveoli of the lung, like most surface epithelia, simultaneously express multiple members of the integrin family, including several with broadly overlapping ligand binding specificities. Although multiple integrins on airway epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
127
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 136 publications
(71 reference statements)
2
127
1
1
Order By: Relevance
“…There is a substantial amount of data to suggest that integrins play a role in epithelial architecture and polarity (Sheppard, 2003;Zegers et al, 2003), but the data are conflicting regarding the precise roles. Experiments using 3D epithelial cysts demonstrated a role for integrins in orienting the direction of polarity, but not for establishing distinct apical and lateral membrane domains (Wang et al, 1990;Ojakian and Schwimmer, 1994).…”
Section: Morphogenesis In the Absence Of Integrinsmentioning
confidence: 99%
“…There is a substantial amount of data to suggest that integrins play a role in epithelial architecture and polarity (Sheppard, 2003;Zegers et al, 2003), but the data are conflicting regarding the precise roles. Experiments using 3D epithelial cysts demonstrated a role for integrins in orienting the direction of polarity, but not for establishing distinct apical and lateral membrane domains (Wang et al, 1990;Ojakian and Schwimmer, 1994).…”
Section: Morphogenesis In the Absence Of Integrinsmentioning
confidence: 99%
“…Molecular mechanisms contributing to these events are complex and include misregulation of the transforming growth factor (TGF)-␤ axis, aberrant ECM remodeling, and altered expression and function of cell adhesion receptors of the integrin superfamily. [1][2][3][4][5] Recent studies have revealed important regulatory functions of several integrins and associated molecules in renal epithelial and mesenchymal cells. 3,6 -8 Among the integrins whose expression is strongly increased in renal disease is the TGF-␤-inducible integrin ␣v␤6.…”
mentioning
confidence: 99%
“…Moreover, Sheppard 2003 showed that integrinβ4 expression was clearly elevated after airway epithelialinjuryand could be detected in many cell types, which suggest that integrin β4 might be involved in the repair processes of airway epithelium (Sheppard 2003). Xiang et al, 2014 found thatmutations in 5̄ flanking region of integrin β4 gene result in reduced integrin β4 expression, and that it was related to increased risk of asthma (Xiang et al, 2014).…”
Section: ‫ـــــــــــــــــــــــــــــــــــــــــــــــــ‬ ‫ـــــــmentioning
confidence: 99%